THE PERSPECTIVE OF CONTEMPORARY FIQH ON GENITAL SURGERY: BETWEEN MEDICAL NECESSITY AND SHARIA NORMS - Robiah, Robiah; Sugiarto, Wira; Norwahyudi, Tri; Maharani, Siti; Hakiki, Nurfatin; Maisarah, Alya; Laili, Nurul; Amira, Nur; Julita, Tria; Ramadhani, Dewi Puspa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The increasing phenomenon of genital reassignment surgery in the modern era has sparked debate between medical necessity and Islamic legal principles. In the field of contemporary fiqh, this issue is crucial to study as it relates to preserving the natural disposition (fitrah) created by Allah and ensuring human well-being (maslahah). The aim of this research is to examine contemporary fiqh perspectives on the legal rulings regarding genital reassignment surgery and to distinguish between medically permissible procedures and those prohibited due to personal motives. Using a literature study method and a descriptive approach, this study explores various scholarly sources, including journals, books, and articles, to highlight the importance of contemporary fiqh views on genital surgery. The findings indicate that Islam permits genital surgery when intended for healing or correcting congenital abnormalities (khuntsa) and restoring organ function, but prohibits it when performed solely to change one’s gender identity. Based on the 1980 fatwa issued by the Indonesian Ulema Council (MUI), such procedures do not alter a person’s legal gender status. Therefore, contemporary fiqh emphasizes the importance of maintaining a balance between advancements in medical science and the principles of Sharia in determining the legal status of genital surgery.